Estudo da geração dos resíduos da construção civil (RCC) em empreendimento habitacional de interesse social no município de Taquaritinga-SP - Soares, Diego Henrique (2015)
The construction industry is the largest consumer of natural resources in their activities. It is estimated that a square meter of construction of a building is consumed an average of one ton of materials, which explains the use of large amounts of cement, sand, gravel, and other inputs during its construction process. Furthermore, the construction is the industry which produces more waste. In Brazil, this situation is aggravated by the construction technology normally applied in new buildings, especially in works of social interest. In these projects, the traditional process of implementation combined with poor quality of production management favors large losses and physical resources waste, which ultimately generate huge amounts of construction waste (RCC) in the beds. For all these reasons, the diagnosis of RCC generation in housing projects of social interest is of great importance, since it can support management strategies of material consumption to reduce waste and costs. In this sense, this paper aims to study the generation of waste from the construction of a housing project of social interest in the city of Taquaritinga-SP, with special focus on the generation rate (kg / m²) of this type of venture. The methodology will be held bibliographical and documentary reviews of the object of study work, and methodologies used by other authors in previous studies to obtain the generation of RCC and their respective generation rate per square meter. It should be noted that in developed countries, this waste production indicator from new construction is around 50 kg / m2, well below the Brazilian indices that revolve around 150 kg / m2. This study showed the rate of 226,28kg / m², demonstrating that the enterprise is slightly above the Brazilian indices. With the completion of this research, we hope to obtain important results for the area of social housing, as the studies of RCC does not include rates for this type of residential development, unlike the indexes extracted in vertical buildings or even reform and demolitions.